(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article proposes a current debate on scenic space. The Brazilian artist Hélio Oiticica treated the space and the notion of environmental art in his inventions, through the approximation of the performance, with attention to the body and the social life. The artist subverted the limits of artistic languages in order to experience the conflicts between art and reality. By coining the notion of self-theater, it is possible to conclude, along with other authors, that Oiticica built a path from screens to bodies, considering the establishment of the environment through the architectural dimension that was triggered by his interest in three-dimensionality. Then he will deal with the liberation of color from static supports until the understanding of space as a social phenomenon along with the radical opening for the invention of other participants in his propositions, going beyond participation.